Performance Monitoring Office of Financial Management And Asset Majalengka of Indonesia - Wikusna, Wawa; Yuniarsa, Haris Y; Rahmatika Damayanti, Bella (International Journal of Engineering and Technology, 2019)
Each the work unit in the Department of Finance and Asset Management (DPKAD) Majalengka in Indonesia required to have a work program that is made in the form of scheduled activities planned, directed, integrated, and scalable to guide the implementation of the work in one fiscal year. In order for the implementation of the work program in accordance with the target, it is necessary to control and supervision of the planning, evaluation, and reporting DPKAD Majalengka. All long, monitoring the implementation of the work program only based on documents submitted activity reports after the event is completed. There is no control and early warning to employees about the schedule of activities, so many activities that late in implementation. Measurement of program performance work the work unit is difficult because basih shaped paper based reports. This research was conducted to develop a web-based application monitoring the performance of the Department of Finance and Asset Management (DPKAD) Majalengka in Indonesia. Applications built using Software Development Life Cycle with the waterfall model, using the programming language PHP framework CodeIgniter, MySQL database, and it is equipped with SMS broadcast. Hopefully, with this application is expected data management work program, including data proposed work programs, the control of the implementation schedule of activities, reporting on the implementation activities and outcomes measurement program can work better quality.Â